Apsara figure on a pillar - Temples of India Project Team (Jio Institute, 2024)
Unlike other apsaras (celestial damsels) carved on the shaft of pillars, she is the only one crowned and holds a cup in her left hand while the right-hand holds something dipped in the cup. Several images from the Harshnath Temple Complex show a cup being held, signifying the nectar of bliss experienced after the completion of tantric-sadhana, while the fingers of the other hands are sometimes dipped into the cup. However, associating an obscure image of a damsel with some tantric connotations might have a little support.